BRANDING PARTAI GERINDRA DI PLATFROM TWITTER DALAM MENGHADAPI PEMILU 2024 SEBAGAI SARANA PERUBAHAN POLITIK KONTEMPORER DI INDONESIA - Nurazizah, Nofuja; Hamid, Rizal Al (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2023)
Changes in the world's political climate began to be felt as going hand in hand with the rapid growth of technological advancements. Communication as a means in lives as initial capital is included in political life in the contemporary era. The emergence of various platforms of social media is pointed as a sign of technological success in this contemporary era. Political discourses started to shift from what was then from mouth-to-mouth, now seem to turn into discourses from one account to another. Thereby changed the political strategy from face-to-face meeting, which also made the branding of political parties nowadays be done with more flexible manner via online network that is able to gain access across various social media platforms. However, a topic of discussion that currently has the most frequent critical approach in such a critical manner, while also political issues, can be found with utmost ease and gain public responses critically throughout one of the most popularly accessed, reaching more than billions of interaction in daily use, the social media platfrom with the name Twitter.